The Effect of Sensory Stimuli With a Familiar Voice and Patient's Auditory Preferences on the Level of Consciousness of Brain Injury Patients Admitted to Intensive Care Units - Sahar Vanoni; Fatemeh Salmani; Mina Jouzi (Iran University of Medical Sciences, 2021)
Background & Aims: Most patients with brain injury experience coma based on the severity of the lesion. One of the complications that threaten patients with coma in intensive care units is the risk of sensory deprivation. Frequent sensory stimulation can be helpful in rehabilitation and increasing the level of consciousness of these patients. This study aimed to determine the effect of sensory stimuli with a familiar sound and patient's auditory preferences on the level of consciousness of patients in coma admitted to intensive care units in selected hospitals in Ahvaz City, Iran. Materials & Methods: The present study is quasi-experimental that was performed on 45 patients admitted to the intensive care unit of selected hospitals in Ahvaz City in 2021. Sampling was performed for six months. The patients who met the inclusion criteria were divided into two intervention groups and one control group by the permutation randomization method. For patients of the first group (hearing stimulation with a familiar voice) and the second group (auditory stimulation with the patient's preference voice), recorded sound was played with a tape recorder for 15 minutes for 3 days twice a day (6 times in total) at 10 AM and 3 PM. Routine care and sounds were provided for the control group. The level of patients' consciousness in three groups was measured by GCS scale 15 minutes before and 15 minutes after the intervention. Results: The study results showed that the mean level of consciousness of the auditory preferences and familiar voice groups after the intervention was significantly higher than that in the control group (P<0.05). But there was no significant difference between the two groups of auditory preferences and familiar voice (P>0.05). Conclusion: Considering that the effect of a familiar voice and auditory preferences has been more than unfamiliar sound, it is recommended to provide a program of auditory stimulation with familiar voices and auditory preferences for comatose patients in intensive care units.